Postoperative analgesia: a comparison of intravenous on-demand fentanyl with epidural bupivacaine. - White, W D (1979)
In a randomised trial postoperative pain relief was provided by either epidural injections of bupivacaine or an infusion of fentanyl adjusted by the patient to achieve adequate pain relief. Both techniques produced satisfactory analgesia without respiratory depression after peripheral arterial surgery. The technique of infusing intravenously a potent analgesic in a dose adjusted by the patient appears to offer several advantages in postoperative care.